The Effect of Relocating Street Hawkers on Urban Vitality in the Malioboro Tourism Area, Yogyakarta - Eva Sanchia Janita; Woerjantari Kartidjo (Fakultas Seni Rupa dan Desain ITB, 2023)
Since the 1970s, street hawkers have considered Malioboro an icon of the city of Yogyakarta. Malioboro has become increasingly crowded. Seeing this condition, a decision was made to relocate the street hawkers from the Malioboro corridor. This decision has pros and cons; some consider street hawkers to be a place for creativity, a sector that greatly affects the level of crowds and is the main attraction for the Malioboro area. However, few people consider it a barrier to the original face of the Malioboro corridor. Urban vitality is an important aspect of increasing visitor interest; it relates to comfort, security, safety, and fun as the main indicators. This study aims to examine the impact of the relocation decision on the vitality of Malioboro as a tourist area. Using qualitative methods, this study compared the reality through field surveys and online questionnaires that had been distributed for one week to a total of 61 respondents who had ever visited Malioboro with the theory of urban vitality and urban tourism precincts. To get a conclusion on whether the Yogyakarta city government’s decision to relocate the street hawkers from Malioboro Street can maintain or even reduce Malioboro’s urban vitality.